Respuesta :

Answer:

x = -7 , x = 2

Step-by-step explanation:

[tex]x^2 + 5x -1 4= 0\\\\x^2 + 7x -2x - 14 = 0\\\\x(x + 7) -2(x + 7) = 0\\\\(x+7)(x-2) = 0\\\\x+ 7 = 0 , \ x - 2 = 0 \\\\x = - 7 , \ x = 2[/tex]

Answer:

x = - 7, x = 2

Step-by-step explanation:

Solve by factoring , that is

x² + 5x - 14 = 0

Consider the factors of the constant term (- 14) which sum to give the coefficient of the x- term (+ 5)

The factors are + 7 and - 2 , since

7 × - 2 = - 14 and 7 - 2 = + 5 , then

(x + 7)(x - 2) = 0 ← in factored form

Equate each factor to zero and solve for x

x + 7 = 0 ⇒ x = - 7

x - 2 = 0 ⇒ x = 2